Deep learning-based classification of multiple fundus diseases using ultra-widefield images - Duan, Ming-Ming; Tu, Xiang (Frontiers in Cell and Developmental Biology, 2025)
PurposeThis study aimed to develop a hybrid deep learning model for classifying multiple fundus diseases using ultra-widefield (UWF) images, thereby improving diagnostic efficiency and accuracy while providing an auxiliary tool for clinical decision-making.MethodsIn this retrospective study, 10,612 UWF fundus images were collected from the JiuJiang No. 1 People’s Hospital and the Seventh Affiliated Hospital, Sun Yat-sen University between 2020 and 2025, covering 16 fundus diseases, including normal fundus, nine common eye diseases, and six rare retinal conditions. The model employed DenseNet121 as a feature extractor combined with an XGBoost classifier. Gradient-weighted Class Activation Mapping (Grad-CAM) was used to visualize the model’s decision-making process. Performance was evaluated on validation and external test sets using accuracy, recall, precision, F1 score, and AUC-ROC. The model’s diagnostic accuracy was also compared with that of junior and intermediate ophthalmologists.ResultsThe model demonstrated exceptional diagnostic performance. For common diseases such as retinal vein occlusion, age-related macular degeneration, and diabetic retinopathy, AUC values exceeded 0.975, with accuracy rates above 0.980. For rare diseases, AUC values were above 0.970, and accuracy rates surpassed 0.998. Grad-CAM visualizations confirmed that the model’s focus areas aligned with clinical pathological features. Compared to ophthalmologists, the model achieved significantly higher accuracy across all diagnostic tasks.ConclusionThe proposed deep learning model can automatically identify and classify multiple ophthalmic diseases using UWF images. It holds promise for enhancing clinical diagnostic efficiency, assisting ophthalmologists in optimizing workflows, and improving patient care quality.